Relation between Knowledge and Mother’s Occupation with Growth and Development of Children between Ages 5-6 in Tk At-Taqwa Cimahi - Yuniarti, Sri (KnE Life Sciences, 2021)
In Indonesia, 45.7% toddlers experienced growth and development disorders. As a candidate for the nation’s next generation, the quality of their growth and development needs serious attention. Knowledge and awareness of mothers play snificant role towards child growth and development. Mother’s occupation, in general, can depict the broadness of the mothers knowledge. In other words, the mother’s occupation can affect the growth and development of their children. This study aims to determine the relationship of mother’s knowledge and occupation with growth and development in children aged 5-6 years at At-Taqwa Cimahi Kindergarten in 2016. The research method used is correlative with cross-sectional design. Samples were 47 mothers with a total sampling technique. Data was obtained by using amultiple choice researc questionnaire for mother and analyzed by univariate and bivariate method with Chi-Square test. The majority of respondents had good knowledge (57.4%), most did not work (55.3%), most of the growth of their children was normal (61.7%) and most of their children’s development was doubtful (55.3%). There is no relationship between mother’s knowledge with the growth of children (p value =, 1.00). There is a relationship between mother’s knowledge and child development in (pValue = 0.01), between mother’s occupation with the growth of children (p Value = 0.01) and also between mother’s occupation and child development (p Value = 0.003). It is recommended that parents broaden their knowledge as effort to develop children’s growth and development abilities that can be optimized by stimulation. Keywords: Cross-sectional, development, employment, growth, knowledge